STUDI KOMPARASI ANTARA EKSPERIMEN NYATA DENGAN EKSPERIMEN SIMULASI TERHADAP PEMAHAMAN FISIKA PADA POKOK BAHASAN GERAK HARMONIK SEDERHANA - Salim, Muhammad Barkah (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Providing material in theory and experiments in physics learning to students is very important and must be balanced. Besides that students are aware of a concept that has been created by scientists in physics, but also clear and understood the concept both theoretically and experimentally. In this study, will compare student learning outcomes after a given learning in real experiments and simulation experiments on simple harmonic motion of the subject.Data collection method used is the questionnaire method tests. Test method consists of pretest and posttest are used to determine students learning achievement physics. Test instruments used are validity with product moment correlation technique, reliability testing with formula Kuder-Richardson 20 (KR-20), difficulty level test, and test different power. For the prerequisite data analysis in this study to test for normality using the formula Chi-Square and homogeneity test using Bartletts test. The data obtained are then processed with the hypothesis test using t-test formula.The results of data analysis showed that there are significant differences between real experimental learning methods with experimental simulation of the physics students achievement of learning comprehension. This is indicated by the acquisition of the t value of 2.460 while ttable at 5% significance level with 32 degrees of freedom is 1.691. The increase in the average score of student achievement (posttest) showed that student achievement using real experimental method 1.77 higher than on student achievement using simulation experiments 0.74, so the proposed hypothesis can be accepted.Â Â